2017
DOI: 10.1142/s0219455417500134
|View full text |Cite
|
Sign up to set email alerts
|

Damage Assessment of Two-Way RC Slab Subjected to Blast Load Using Mode Approximation Approach

Abstract: Significant research efforts have been invested on studying the response and damage of structures subjected to blast loads for better life and property protections. The single-degree-of-freedom (SDOF) approach has been widely adopted to simplify the structural response analysis for engineering design purpose. However, such an approach under certain circumstances oversimplifies the structural behavior and might not give reliable predictions of structural responses to blast loads. On the other hand, although det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Rise in terrorism and increase in accidental detonation events highlight the need for the blast-resistant design of conventional structures (Anas et al, 2021b; Kyei and Braimah, 2017). Anumber of researchers (Alonso et al, 2011; Anas et al, 2020a, 2020b, 2021bbib_Anas_et_al_2020abib_Anas_et_al_2020bbib_Anas_et_al_2021b; Castedo et al, 2015; Huang et al, 2016; Li et al, 2011, 2015a, 2015b, 2020bib_Li_et_al_2011; Li and Hao, 2014bib_Li_et_al_2015abib_Li_et_al_2015bbib_Li_et_al_2020; Lin et al, 2014; Wang et al, 2013; Wu and Hao, 2005bib_Wu_et_al_2009abib_Wu_et_al_2009b; Xu and Lu, 2006; Yao et al, 2016; Zhang et al, 2013; Zheng et al, 2018; Zhao and Chen, 2013; Zhao et al, 2012, 2018, 2019a, 2019bbib_Zhao_et_al_2012bib_Zhao_et_al_2018bib_Zhao_et_al_2019abib_Zhao_et_al_2019b; Zhou and Hao, 2009; Zhou et al, 2008) have identified failure of reinforced cement concrete (RCC) slabs under explosion loading as a potential threat to the building infrastructure. Failure of top story columns and slab due to a confined gas explosion resulting partial collapse of a residential building in Central Russia (Anas et al, 2021b; Myers et al, 2004), the collapse of intermediate columns supporting a slab causing severe damage to the apartment building in the western Germany city of Wuppertal (Myers et al, 2004), and internal gas explosion in Maryland buildings (Columbia) leading to progressive collapse are some of the examples of accidental explosions (Figure 1) (Nash et al, 1995; Netten and Dewey, 1997; Osteraas, 2006).…”
Section: Review Of the Latest Literaturementioning
confidence: 99%
“…Rise in terrorism and increase in accidental detonation events highlight the need for the blast-resistant design of conventional structures (Anas et al, 2021b; Kyei and Braimah, 2017). Anumber of researchers (Alonso et al, 2011; Anas et al, 2020a, 2020b, 2021bbib_Anas_et_al_2020abib_Anas_et_al_2020bbib_Anas_et_al_2021b; Castedo et al, 2015; Huang et al, 2016; Li et al, 2011, 2015a, 2015b, 2020bib_Li_et_al_2011; Li and Hao, 2014bib_Li_et_al_2015abib_Li_et_al_2015bbib_Li_et_al_2020; Lin et al, 2014; Wang et al, 2013; Wu and Hao, 2005bib_Wu_et_al_2009abib_Wu_et_al_2009b; Xu and Lu, 2006; Yao et al, 2016; Zhang et al, 2013; Zheng et al, 2018; Zhao and Chen, 2013; Zhao et al, 2012, 2018, 2019a, 2019bbib_Zhao_et_al_2012bib_Zhao_et_al_2018bib_Zhao_et_al_2019abib_Zhao_et_al_2019b; Zhou and Hao, 2009; Zhou et al, 2008) have identified failure of reinforced cement concrete (RCC) slabs under explosion loading as a potential threat to the building infrastructure. Failure of top story columns and slab due to a confined gas explosion resulting partial collapse of a residential building in Central Russia (Anas et al, 2021b; Myers et al, 2004), the collapse of intermediate columns supporting a slab causing severe damage to the apartment building in the western Germany city of Wuppertal (Myers et al, 2004), and internal gas explosion in Maryland buildings (Columbia) leading to progressive collapse are some of the examples of accidental explosions (Figure 1) (Nash et al, 1995; Netten and Dewey, 1997; Osteraas, 2006).…”
Section: Review Of the Latest Literaturementioning
confidence: 99%
“…The P-I diagrams in the dynamic and impulsive districts are also sensitive to various influencing factors. Many attempts have been implemented to tackle the variation of the P-I diagram, such as the piecewise equations regarding multiple failure modes (Huang et al, 2017; Li and Hao, 2014; Xu et al, 2014), the pressure–impulse band (PIB) covering the reinforcing details and eccentric actions (El-Dakhakhni et al, 2009), and the probabilistic diagrams using the Monte Carlo method (Parisi, 2015). Meanwhile, there were also many diagrams for steel structures (Al-Thairy, 2016; Shi et al, 2017), polyvinyl butyral (PVB)–laminated float glass window (Zhang et al, 2013), brick masonry (Elliot et al, 1992) and some new-fashioned structural forms made of advanced materials (Liao et al, 2019; Zhang et al, 2017).…”
Section: Blast-induced Damage Identificationmentioning
confidence: 99%
“…Based on a number of previous field blasting test and laboratory testing results on RC structures, different failure criteria have been proposed by different researchers to quantify structural damage corresponding to different failure modes (Huang et al, 2017; Ma et al, 2007; Yu and Jones, 1991). Since the maximum ductile plastic deformation is usually developed at the mid-span of a RC beam for flexural dominated response, the ratio of central deflection to half-span length is normally utilized to define the criteria for flexural bending failure; while the averaged shear strain at supports is employed to define the direct shear damage criterion since the maximum shear plastic deformation usually appears near the supports.…”
Section: Determination Of Analysis Parameters and Failure Criteriamentioning
confidence: 99%